HUBUNGAN ANTARA METODE BIMBINGAN KONSELING DAN PERILAKU SISWA KELAS X SEMESTER GENAP DI SMK NEGERI 1 TUALANG - Tengku Rita (Jurnal Pendidikan, 2020)
The purpose of this research was to know the method of counseling guidance provided by counselors to students of SMK Negeri 1 Tualang and to know the relationship of counseling guidance with the behavior of students of SMK Negeri 1Tualang. The data collection in this study was conducted using qualitative techniques by distributing questionnaires to respondents. The results showed that the absence of relationship counseling guidance methods namely lecture methods, question and answer methods, and brainstorming methods of changing student behavior, namely discipline behavior, diligent behavior, polite behavior, and obedient behavior. Regarding the respondent's assessment of the quality of counseling guidance methods applied with the approach used to students, most respondents responded inappropriately, and scheduled consultations will be able to increase the interest in student counseling.